Book Publishing in Croatia Today - Jelušič, Srečko (Javnost-The Public, 2004)
The author argues for the need to introduce data collecting and research methods as basic means by which to plan the development of a book industry in Croatia. The article starts by describing the wider social context in contemporary Croatia and identifying the main characteristics and trends in the post-war country, with emphasis on the dominant values of Croatian society and its book market. Recent and actual book market characteristics are described based on publisher activities, state support for book publishing, and legal activities in regard to copyright and education. Attention is given to the media presentation of book production.